Skin and gut imprinted T helper cell subsets exhibit distinct functional phenotypes in central nervous system autoimmunity - Hiltensperger, Michael (Nat Immunol, 2021)
Multidimensional single cell-analyses of T cells have fueled the debate about either extensive plasticity or “mixed” priming of T helper cell subsets in vivo. Here, we developed an experimental framework to probe the idea that the site of priming in the systemic immune compartment is a determinant of T helper cell-induced immunopathology in remote organs. By site-specific in vivo labeling of antigen-specific T cells in inguinal (i) or gut draining mesenteric (m) lymph nodes, we show that i-T cells and m-T cells isolated from the inflamed central nervous system in a model of multiple sclerosis are distinct. i-T cells were Cxcr6(+) and m-T cells expressed P2rx7. Notably, m-T cells infiltrated white matter while i-T cells were also recruited to grey matter. Therefore, we propose that the definition of T helper cell subsets by their site of priming might guide an advanced understanding of T helper cell biology in health and disease.